Tinjauan Elevasi Puncak Bangunan Seawall di Pantai Galesong Utara - Mutiara, Indra (Politeknik Negeri Ujung Pandang, 2018)
This study aims to review the use of vertical datumand determine the elevation of seawall constructions based on thesea level design. The sea level design used as a vertical referenceis MSL and LWS. The elevation of the seawall construction fromthe two references above then compared to the elevation of theseawall construction listed in the as built drawing documentduring construction. The MSL value is obtained from the tidalanalysis by using Doodson method based on direct observationfor 39 hours, while the LWS value is obtained by taking intoaccount the position of the range of tide at Tide Station inMakassar. Seawall elevation is obtained by terrestrialmeasurements using the Total Station by measuring the height ofthe top position of the seawall construction against the sea leveldesign through the Bench Mark. The seawall top elevation datacollection is done every one meter along 274 meters. The resultsobtained from measuring seawall construction elevation are +2,251 meters if using reference to MSL and +2,911 meters if usinga reference to LWS, while the elevation in the as built drawingdocument is +4,000 meters unknown what vertical reference isused as a reference.